Behavioral Disorders Associated with GnRH Agonist Therapy - Akintola, K. O.; Omoruyi, A. O.; Foster, M. B.; Kingery, S. E.; Wintergerst, K. A. (Experimental and Clinical Endocrinology & Diabetes Reports, 2014)
A number of adverse effects have been described with the use of gonadotropin releasing hormone agonist (GnRHa) therapy in children namely, localized reaction at the site of injection such as pain, erythema, rash, infection or abscess formation and systemic effects such as headache, syncope, fever, or weight gain. These effects have been reported in fewer than 2% of patients receiving GnRHa.While psychological changes have been reported in adult women receiving therapy, these types of adverse events have not been well documented in children. In this report, we describe 3 distinct cases of acute behavioral problems including emotional lability and aggression that were observed in patients being treated with GnRHa implant for central precocious puberty and with dramatic improvement of psychologic changes upon the discontinuation of therapy.
Keywords: gonadotropin; gonadotropin releasing hormone agonists (GnRHa); precocious puberty (PP); central precocious puberty (CPP); hypothalamic-pituitary-gonadal (HPG) axis; kisspeptin